Biomarker Preservation and Survivability Under Extreme Dryness and Mars-Like UV Flux of a Desert Cyanobacterium Capable of Trehalose and Sucrose Accumulation - Fagliarone, Claudia; Napoli, Alessandro; Chiavarini, Salvatore; Baqué, Mickael; de Vera, Jean-Pierre; Billi, Daniela (Frontiers in Astronomy and Space Sciences, 2020)
Unravelling how long life can persist under extreme dryness and what kind of environmental extremes can be faced by dried microorganisms, is relevant to understand Mars habitability and to search for life on planets with transient liquid water availability. Since trehalose and sucrose stabilize dried anhydrobiotes, an in silico survey of the genome of the desert cyanobacterium Chroococcidiopsis sp. CCMEE 029 was performed to identify pathways for trehalose and sucrose biosynthesis. The expression of the identified genes was induced in response to desiccation and trehalose and sucrose accumulation was detected in dried cells. This adaptation strategy enabled viability and biomarker permanence under extreme dryness and Mars-like UV flux. Chroococcidiopsis survivors were scored in 7-year dried biofilms mixed with phyllosilicatic Mars regolith simulant and exposed to 5.5 x 103 kJ/m2 of a Mars-like UV flux. No survivors occurred after exposure to 5.5 x 105 kJ/m2, although in dead cells, photosynthetic pigments and nucleic acids, both DNA and RNA, were still detectable. This suggested that dried biofilms mixed with phyllosilicatic Martian regolith simulant are suitable candidates to identify biosignatures embedded in planetary analogue minerals as planned in the future BioSigN (BioSignatures and habitable Niches) space mission to be performed outside the International Space Station.